2014
DOI: 10.1080/03057925.2013.871399
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the menstruation and education experiences of girls in Tanzania, Ghana, Cambodia and Ethiopia

Abstract: The barriers to menstrual hygiene management faced by adolescent schoolgirls in low-income countries are gaining interest at practice and policy levels. The challenges include inadequate water, sanitation and disposal facilities for the management of menses with privacy and dignity, and insufficient guidance to help girls feel confident in attending school during menses. The studies described here aimed to examine how menarche impacts the lives of schoolgirls in three low-income countries (Ghana, Cambodia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
128
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(153 citation statements)
references
References 25 publications
8
128
0
2
Order By: Relevance
“…Many participants described a process of transitioning to womanhood that unfolded in a series of developmental stages beginning with the physical transformations that occur during puberty such as menarche (see also Mensch, Bruce, and Greene 1998; Sommer 2009; Sommer et al 2015). Puberty also set in motion a series of behavioural changes including: increased attention to one’s appearance because of a burgeoning interest in boys, more domestic responsibilities, beginning sexual activity, and for many, giving birth.…”
Section: Resultsmentioning
confidence: 99%
“…Many participants described a process of transitioning to womanhood that unfolded in a series of developmental stages beginning with the physical transformations that occur during puberty such as menarche (see also Mensch, Bruce, and Greene 1998; Sommer 2009; Sommer et al 2015). Puberty also set in motion a series of behavioural changes including: increased attention to one’s appearance because of a burgeoning interest in boys, more domestic responsibilities, beginning sexual activity, and for many, giving birth.…”
Section: Resultsmentioning
confidence: 99%
“…A study done on comparison of the menstruation and education experiences of girls in Africa reported 84% of girls in Afghanistan never wash their genital areas, where as 80% of girls in Afghanistan use water but no soap for washing their menstrual protection and 30% of girls in Malawi do not use the latrine when menstruating. This was also noted by 20% of women in communities in India [12,13]. A study in Nigeria on the practice of menstrual hygiene of girls 73 (60%) changed sanitary pads three times a day,whereas similar studies reported 11% of girls in Ethiopia and 60% of girls in India only change their menstrual cloths once a day [2,14].…”
Section: Introductionmentioning
confidence: 97%
“…Girls in rural Ethiopia also expressed a hesitancy to buy sanitary pads in public shops due to the cultural or social implications of becoming a woman in Ethiopian society (e.g. readiness to marry and have children) [12].…”
Section: Introductionmentioning
confidence: 99%
“…[1921] Taboos around the topic mean many adolescent girls are unprepared for menarche, and that management practices are not discussed openly. [19, 20, 22] In the confined school environment, with a lack of access to adequate latrines or separate latrines for males and females, menstrual management presents a significant challenge.…”
Section: Introductionmentioning
confidence: 99%